Enteral feeding and its impact on the gut immune system and intestinal mucosal barrier - Szefel, Jarosław; Kruszewski, Wiesław J.; Buczek, Tomasz (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Enteral feeding is the preferred method of nutritional therapy. Mucosal lack of contact with nutrients leads do lymphoid tissue atrophy, immune system functional decline, and intensification in bacterial translocation. Currently, it is assumed that microbiome is one of the body organs that has a significant impact on health. The composition of microbiome is not affected by age, sex, or place of residence, although it changes rapidly after diet modification. The composition of the microbiome is determined by enterotype, which is specific for each organism. It has a significant impact on the risk of diabetes, cancer, atherosclerosis, and other diseases. This review gathers data on interaction between gut-associated lymphoid tissue, mucosa-associated lymphoid tissue, microbiome, and the intestinal mucosal barrier. Usually, the information on the aforementioned is scattered in specialist-subject magazines such as gastroenterology, microbiology, genetics, biochemistry, and others.